2023
DOI: 10.3390/nu15030545
|View full text |Cite
|
Sign up to set email alerts
|

Relative Validity and Reproducibility of Dietary Measurements Assessed by a Semiquantitative Food Frequency Questionnaire among Chinese Healthy Adults

Abstract: This study aimed to evaluate the relative validity and reproducibility of a semiquantitative food frequency questionnaire (SFFQ) in adult populations in China. Among the 49 recruited healthy participants (age range: 20–60 years), the relative validity of a 79-item SFFQ was assessed in two ways: (1) by comparing its dietary intake estimates with those from the average measurements of three inconsecutive 24 h dietary records (24-HDRs); and (2) by comparing its estimates of dietary fatty acids with the measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…First, the current analysis relied on questionnaires to collect data on dietary intake and oral conditions. Despite that the validation study of our food frequency questionnaire showed robust reliability and validity [21], recall bias relying on participants' ability to recall their food intake frequency and quantity over a specific period is quite possible. Meanwhile, we did not collect information on visits to dental professionals or oral hygiene practices or medication.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, the current analysis relied on questionnaires to collect data on dietary intake and oral conditions. Despite that the validation study of our food frequency questionnaire showed robust reliability and validity [21], recall bias relying on participants' ability to recall their food intake frequency and quantity over a specific period is quite possible. Meanwhile, we did not collect information on visits to dental professionals or oral hygiene practices or medication.…”
Section: Discussionmentioning
confidence: 98%
“…Dietary data were collected using a validated 79-item food frequency questionnaire [21], which assessed the consumption frequencies and the portion sizes of food items consumed by the participants over the past 12 months. The average daily intake of each food item was calculated by multiplying its daily frequency and the corresponding portion size.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…In a previous meta-analysis of the validity of FFQ among Chinese adults compared with 24HRs, the pooled SCC ranged from 0.28 (edible oil) to 0.62 (milk and dairy products) for food groups, and from 0.34 (manganese) to 0.88 (copper) for nutrients [ 5 ]. In particular, a previous study evaluated a Chinese FFQ with 149 food items among 300 Chinese adults aged 25–64 years in Jiangsu Province and Beijing municipality; the crude correlation coefficients between the FFQ and six-repeated 3 consecutive days-24HRs ranged from 0.15 (nuts) to 0.90 (liquor) for foods (mean r = 0.55) and from 0.22 (vitamin C) to 0.84 (polyunsaturated fatty acid) for nutrients (mean r = 0.56) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis among healthy adults including 130 validation studies worldwide demonstrated that the mean correlation coefficients of nutrients assessed by FFQs was 0.416 compared with the 24-hour dietary recalls (24HRs), and was 0.373 compared with dietary records (DRs), indicating a moderate-to-high validity of using FFQs to assess nutrient intakes, despite some low performance for several specific nutrients [ 4 ]. In another meta-analysis among Chinese free-living adults across 30 validation studies, the pooled correlation coefficients were 0.44 for nutrients and 0.41 for food groups compared with 24HRs; and the corresponding correlation coefficients were 0.35 for nutrients and 0.42 for food groups compared with DRs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires covered socio-demographic characteristics, health-related information, lifestyle information, and the frequency and consumption of various food items. Information regarding dietary consumption was collected through food frequency questionnaire (FFQ) that is widely employed in mainland China 15 , 16 . Participants were required to report their frequency of consumption of various food weekly over the past year, as well as the quantity of each food item consumed during each instance.…”
Section: Methodsmentioning
confidence: 99%